Alternating ring-opening copolymerization of styrene oxide and maleic anhydride using asymmetrical bis-Schiff-base metal(iii) catalysts. Issue 1 (8th October 2014) - Liu, Dengfeng; Zhang, Xingmei; Zhu, Luqun; Wu, Jing; Lü, Xingqiang
Abstract : The ring-opening copolymerization of styrene oxide and maleic anhydride catalyzed by a series of [M(L n )X] complexes based on the asymmetrical bis-Schiff-base ligands. Abstract : A ring-opening copolymerization of styrene oxide with maleic anhydride was performed by applying a series of asymmetrical bis-Schiff-base metal(iii ) catalysts. The chromium catalyst exhibited the best performance and therefore the catalyst (salen)CrCl (salen = 4-(( Z )-(2-(( E )-3, 5-dibromo-2-hydroxybenzylideneamino)phenylimino)(phenyl)methyl)-1-(4-chlorophenyl)-3-methyl-1 H -pyrazol-5(4 H )-one) (7 ) was chosen for further studies. The investigations on the effect of different co-catalysts on the copolymerization of styrene oxide and maleic anhydride revealed that DMAP showed the highest activity, followed by PPN + Cl −, whereas Ph3 P showed the lowest activity. 1 H NMR and MALDI-TOF-MS spectra of the copolymers formed confirmed the alternating microstructures. The copolymerization of styrene oxide with maleic anhydride bearing a double bond in its structure was shown to be highly dependent on the polymerization condition, type of co-catalyst, monomer to catalyst ratio, temperature and time used in the copolymerization reaction. Applying chain transfer agents, alcohols, resulted in a decrease in molecular weight.